2017
DOI: 10.1038/s41598-017-04556-1
|View full text |Cite
|
Sign up to set email alerts
|

Natural and induced loss of function mutations in SlMBP21 MADS-box gene led to jointless-2 phenotype in tomato

Abstract: Abscission is the mechanism by which plants disconnect unfertilized flowers, ripe fruits, senescent or diseased organs from the plant. In tomato, pedicel abscission is an important agronomic factor that controls yield and post-harvest fruit quality. Two non-allelic mutations, jointless (j) and jointless-2 (j-2), controlling pedicel abscission zone formation have been documented but only j-2 has been extensively used in breeding. J was shown to encode a MADS-box protein. Using a combination of physical mapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…1f and Supplementary Figure 1a). Notably, the Ty1/COPIA RIDER family, which generated insertion mutations with important agronomic implications 21,22,28,29 , contributes the highest number (507) of TIPs overall. Mobilome composition varies substantially among tomato groups and is richest in the genetically diverse SP group (~230 TE families, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1f and Supplementary Figure 1a). Notably, the Ty1/COPIA RIDER family, which generated insertion mutations with important agronomic implications 21,22,28,29 , contributes the highest number (507) of TIPs overall. Mobilome composition varies substantially among tomato groups and is richest in the genetically diverse SP group (~230 TE families, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to form a heterodimer with a second MADS-box protein JOINTLESS and regulate genes involved in pedicelspecific abscission processes including auxin/ethylene regulation, cell wall modifications, and production of several TFs involved in meristem maintenance and development . An additional MADS-box factor SlMBP21 also has been shown to form tetramers with MC and JOINTLESS and also is involved in abscission regulation (Roldan et al, 2017;Soyk et al, 2017). Tomato RIN might also be expected to act in concert with other MADS-box proteins.…”
Section: Expression Of Mads Transcription Factors During Fruit Ripenimentioning
confidence: 99%
“…Interestingly, more recent studies in tomato have elucidated the function of the enigmatic FBP9 subclade genes. It was found that SLMBP21/JOINTLESS2 (J2) is required for the development of the pedicel abscission zone (Liu et al, 2014;Roldan et al, 2017;Soyk et al, 2017). Furthermore, a breakthrough functional study (Soyk et al, 2017) based on both natural and CRISPR-Cas9 -induced mutant alleles showed that the two tomato FBP9 clade genes SLMBP21/J2 and SlMADS1/ENHANCER OF JOINTLESS2 (EJ2) have overlapping functions in meristem maturation and the control of inflorescence branching together with LONG INFLORESCENCE (LIN), the second tomato SEP4-like gene.…”
Section: Petunia Sep/agl6 Expression Analysis and Mutant Identificationmentioning
confidence: 99%
“…While the strongest phenotype was obtained in the tomato triple mutants, analysis of single and double mutants revealed also individual contributions to tomato development: LIN limits internode length and the number of flowers that develop per inflorescence, EJ2 negatively regulates sepal size, while both J2 and EJ2 are involved in the control of branching of the tomato inflorescence (Soyk et al, 2017). In addition, J2 is required for the development of the pedicel abscission zone (Liu et al, 2014;Roldan et al, 2017;Soyk et al, 2017).…”
Section: Implication Of Sep and Agl6 Gene Functions In Floral Organ Imentioning
confidence: 99%